Strategi Pengelolaan Zakat dalam Pencapaian Sustainable Development Goals (SDGs) - Effendi, Bahtiar; Nariah, Siti (Sharia Faculty Islamic Economic Law Study Department, 2023)
This research aims to find out about how the zakat management strategy implemented by LAZISMU Pekalongan Regency in achieving Sustainable Development Goals (SDGs). LAZISMU Pekalongan Regency is one of the credible zakat institutions proven by four times obtaining WTP (unqualified) status. The data collection techniques used in this research include observation, documentation and interviews related to LAZISMU's profile, the potential of LAZISMU's zakat collection through service offices, and the strategy of managing zakat funds related to the achievement of SDGs in the fields of economy, education, and health services. The results showed that in 2022 LAZISMU Pekalongan Regency was able to collect zakat funds amounting to 8 billion. In its management, LAZISMU is able to direct its zakat funds to intersect with sustainable development programs such as economic empowerment, education and health. LAZISMU's economic programs include empowering and providing capital to MSMEs such as training, providing capital assistance, or carts, the farmer rise program, the makeup corner program. In the field of education, there are kindergarten to doctoral scholarships, Teacher Care, LAZISMU go to Campus, and Sang Surya Scholarships. While in the health sector, assistance is provided to patients who cannot afford it, providing free ambulance services for the poor, BPJS health for those not covered by BPJS, preventing and caring for stunting, TB and HIV care in the form of providing food assistance for resistant TB sufferers where most people affected by the disease are people who are classified as poor. Therefore, the role of LAZISMU through the management of zakat funds is very important to continue to be improved in order to create sustainable development for the welfare of the community.